Select medical holdings corp - investment committee paper - Rodrigues, Joana Santa Clara Pedrosa (2021)
The proposed Investment Committee Paper focuses on a potential Leveraged Buy out of Select Medical Holdings Corp, a key company of the United States health care industry operating in Critical Illness Recovery Hospitals, Rehabilitation Hospitals, Out patient Rehabilitation Clinics and Occupational Health Centers. The group initiated a company and market overview to assess the eligibility of Select Medical as an LBO candidate .Future value creation strategies were developed and taken into consideration in the forecast of the operating model. Posteriorly, the group evaluated the company, built an optimal capital structure and assessed potential exit options, calculating the returns for the exit year.